2018
DOI: 10.1007/s00431-017-3082-x
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular catheterization of the brachiocephalic vein: a way to prevent or reduce catheter maintenance-related complications in children

Abstract: BCV catheterization via the US-guided supraclavicular approach may decrease CVC maintenance-related complications in children hospitalized in a PICU. What is Known: • Placement of a central venous catheter (CVC) in children is associated with mechanical risks during insertion, and with infectious and thrombotic complications during its maintenance. • Ultrasound (US)-guided supraclavicular catheterization of the brachiocephalic vein (BCV) is feasible in infants and children. What is New: • This observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 30 publications
4
37
1
3
Order By: Relevance
“…Apart from one catheter obstruction, no long‐term complication was reported in this series. This is in accordance with two previous studies demonstrating lower rates of infection, catheter obstruction, and symptomatic deep vein thrombosis for brachiocephalic venous catheters compared to internal jugular and femoral venous catheters in babies 16,17 . Two of our previous studies demonstrated a poor sonographic view of the right BCV, at times showing only a circular appearance due a particularly steep run (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…Apart from one catheter obstruction, no long‐term complication was reported in this series. This is in accordance with two previous studies demonstrating lower rates of infection, catheter obstruction, and symptomatic deep vein thrombosis for brachiocephalic venous catheters compared to internal jugular and femoral venous catheters in babies 16,17 . Two of our previous studies demonstrated a poor sonographic view of the right BCV, at times showing only a circular appearance due a particularly steep run (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…132 Comparatively, brachiocephalic insertion sites were associated with significantly lower CLABSI and thrombosis compared to jugular and subclavian approaches. 69 Overall, CVAD insertion through the femoral vein was linked to higher risk of thrombosis 51,67,89 but lower complication and infection rates in infants ,5 kg. 85…”
Section: Recommendations For Insertion Insertion Locationsmentioning
confidence: 97%
“…113 Across CVAD types, insertion via the internal jugular in infants and pediatric patients was associated with increased risk of high arterial puncture, 42,113 postoperative chylothorax, 36 thrombosis, 67,69,89 and infection. 42,69 Insertion through the subclavian vein was correlated with an increased risk of high arterial puncture (left-side approaches), 42,113 arrhythmias and misplacement (right-side approaches), 113 malposition and occlusion, 42 postoperative chylothorax, 36 and sepsis. 31 In pediatric oncology patients, subclavian insertion sites had higher rates of thrombosis compared to external jugular and cephalic sites, but there was no difference in rates between right-or left-side insertion sites.…”
Section: Recommendations For Insertion Insertion Locationsmentioning
confidence: 99%
“…Ultrasound-guided cannulation of the BCV is associated with a higher rate of first attempt success and fewer cannulation attempts compared to other approaches [ 231 , 232 ]. The accidental arterial puncture rate was not significantly different between internal jugular and subclavian vein cannulation [ 227 , 228 ], but was lower for BCV cannulation [ 229 ]. The study by Lu et al was not included in this analysis, as BCV cannulation was not ultrasound-guided in 2001 [ 230 ].…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…The study by Lu et al was not included in this analysis, as BCV cannulation was not ultrasound-guided in 2001 [ 230 ]. Very low pneumothorax rates were reported in the various studies (all cases of pneumothorax were observed with classical subclavian vein cannulation); no cases of pneumothorax were observed with the BCV in two case series and one comparative study [ 225 , 226 , 229 ]. Subclavian vein cannulation was associated with higher rates of guidewire misplacement and catheter malposition with a high level of evidence [ 227 , 228 , 231 , 232 ], as access is more direct for femoral veins, right jugular veins and both brachiocephalic veins.…”
Section: Summary Of the Resultsmentioning
confidence: 99%